El Inbound Marketing como estrategia de captación de clientes en el sector gastronómico de Piura, Perú - Castillo Córdova, Giancarlo Sebastián (2024)
The objective of this research was to analyze the contribution of inbound marketing to customer acquisition in the gastronomic sector of Piura in 2024. The study employed an applied methodology, a mixed approach, a non-experimental cross-sectional design, and a descriptive level of analysis. The study sample consisted of 196 customers of restaurants in the city of Piura. The questionnaire was employed as a data collection instrument, with the objective of obtaining information from restaurant customers. The results demonstrated that 46.4% of respondents indicated that restaurants generate pertinent content for dissemination through their various digital media channels, while 50% asserted that the quality of service received significantly influences their perception of the business. It was concluded that inbound marketing benefits restaurants in terms of customer acquisition. However, it is necessary that they continue to strengthen the strategies they already implement so that greater levels of effectiveness can be achieved in this process.